Review of: Samuel K. Cohn, Jr., EPIDEMICS: HATE AND COMPASSION FROM THE PLAGUE OF ATHENS TO AIDS, Oxford: Oxford University Press, 2018, 656 pages. - Konstantinidou, Katerina (The Historical Review/La Revue Historique, 2020)
.